Investigation of Toxoplasmosis in a sample of rheumatoid arthritis patients in Baghdad Governorate (Journal of the College of Basic Education, 2025)
Toxoplasma gondii, a parasite belonging to the phylum Apicomplexa, is an obligate intracellular parasite that infects all nucleated cells. It causes toxoplasmosis, a communicable disease with worldwide prevalence. Toxoplasmosis is one of the most common primary opportunistic infections. T. gondii infection can occur in patients with immunosuppression, autoimmune diseases such as rheumatoid arthritis, organ transplants, and acquired immunodeficiency syndrome (AIDS). The current study aimed to investigate the seroprevalence of T. gondii among rheumatoid arthritis patients attending arthritis clinics in Baghdad hospitals. The study included the collection of 180 blood samples from the beginning of September 2024 to the end of February 2025, with ages ranging from 20 to 60 years, in addition to 60 blood samples from healthy individuals who formed the control group. Blood from all samples under study was separated after being placed in sterile tubes in a centrifuge at 3000 rpm for 5 minutes. The serum was then withdrawn and distributed into 1 ml Eppendorf tubes, each containing 250 microliters. The sample was stored at -20°C in the Parasitology Laboratory of the Sciences department , College of Basic Education, Al-Mustansiriya University, until use. All samples were tested using the Latex Agglutination Test (LA) and Rapid Cassette IgG, IgM Test to diagnose T. gondii infection in rheumatoid arthritis patients. The results of the latex test showed that 39 samples (22%) were positive, while 141 samples (78%) were negative. The control group did not show any positive results for this test, with highly significant differences at the probability level (P≤0.001). As for the results of the immune chromatography test, the number of positive samples reached 75 (42%), compared to 105 (58%) negative samples. The control group did not show any positive results, with highly significant differences at the probability level (P≤0.001). Among the tests used in the study as supportive tests for the diagnosis of rheumatoid arthritis are the rheumatoid factor (RF) and the C-reactive protein (CRP) test. Both the rheumatoid arthritis group with and without toxoplasmosis recorded 100% positive results for the RF and CRP tests, while the control group showed complete negativity for both tests, with highly significant differences at the probability level (P≤0.0001). The study also included an examination of some epidemiological factors associated with infection with Toxoplasma gondii, including gender. The group of rheumatoid arthritis patients with T. gondii exhibited a higher prevalence of females than males, with a percentage of 68% for females and 32% for males. The same was true for the second group, with a percentage of females reaching 79%, which was higher than the percentage of males, which was 21%. As for age, the group of patients with rheumatoid arthritis and T. gondii showed a higher rate of The average age of the rheumatoid arthritis patients who were not infected with T. gondii was 43.11 ± 0.39 years. The ages of the two groups mentioned above were centered within a range of 21-60 years, while the age of the control group did not exceed fifty years with an average of 31.72 ± 2.25 years. The educational level also affected the spread of infections, as highly significant differences appeared at the probability level (P≤0.0001) between the groups under study, as most of the individuals of the rheumatoid arthritis group infected with T. gondii were centered with a high frequency among the uneducated at a rate of 28% and the primary education level at a rate of 37%, while most of the samples of the rheumatoid arthritis group patients who were not infected with T. gondii were based on the levels (uneducated - primary - intermediate) with a total rate of 77%, while most of the samples of the control group extended Control at the secondary and university levels with a total percentage of 65%.